An evaluation of esp programs at felte, ulis, vnu by QH2008 English translation and interpretation students = Đánh giá của sinh viên khóa QH2008 hệ Tiếng Anh phiên dịch, khoa Tiếng Anh sư phạm, đại học ngoại ngữ, đại học quốc gia hà nội về chương trình Tiếng Anh chuyên ngành - Bùi, Thị Bích Thảo (2021)
This study was carried out with an attempt to have an insight into Translation and Interpretation students‟ evaluation of the ESP Programs at FELTE, ULIS, VNU. The study is composed of three main parts: Introduction, Development, and Conclusion. Firstly, the introduction discusses the rationale, aims and significance, research questions, method of the study, scope of the study, and design of the study. Secondly, the development includes three chapters. Chapter I, “Literature Review”, focuses on theoretical background of the study. Chapter II, “An Overview of English for Economics and English for Finance and Banking at FELTE, ULIS, VNU”, presents background information about English for Economics and English for Finance and Banking at FELTE, ULIS, VNU. And chapter III, “The Study”, describes the methodology employed to collect data for the study, reports on the learners‟ evaluation of the ESP programs at FELTE, ULIS, VNU and their needs, shows the major findings and provides some suggestions to improve the current ESP program for Economics and ESP program for Finance and Banking at FELTE, ULIS, VNU. Finally, the study ends with the conclusion which refers to what have been found out from the study and the limitations and suggestions for further study